Analysis of heat waves temporal fluctuation in North - West region of Iran and their relationship with greenhouse gases and global land-ocean temperature anomalies (تحقیقات کاربردی علوم جغرافیایی)
The heat waves today are one of the most important climatic hazards in the world. According to many scientists, the Severe and frequent occurrence of heat waves in recent years has been due to the emission of greenhouse gases and consequent increased global warming. The purpose of this study is to investigate changes in the frequency and intensity of heat waves As well as their relationship with Global land-ocean temperature anomalies and greenhouse gases in the north-west of Iran. At First, maximum temperature of two meters of the surface during the period from 1851 to 2014 for 164 years was obtained from NASA’s website, then the maps of heat waves was drawn and extracted. Then, we analyzed and evaluated the frequency and severity of the heat waves, as well as changes in the annual, decade, fifty years old fluctuations and their centenary were analyzed. To achieve the research objectives, Pearson and Spearman correlation methods, linear and polynomial regression and non-parametric Mann-Kendall test were used. The results showed that the frequency of occurrence of heat waves in the considered period interval is incremental and relevant, and the most frequency of occurrence was in decades. Also the intensity of the heat waves is associated with a relatively significant increase, and the most intense heat waves occurred in the decades of the late 20th and early 21st century until the present period. The results of the correlation coefficients indicated that the intensity and frequency of the heat wave incidence have a positive and significant correlation with the Global land-ocean temperature anomalies. The results of investigating the relationship between frequency and intensity of heat waves with 4 important greenhouse gases, including: (CO2, CH4, N2O, SF6), showed that, except for the positive and significant correlation of carbon dioxide gas with the most severe  heat waves in June, There was no meaningful relationship between them. The results of the Mann-Kendall test indicate an incremental and significant increase in the frequency and intensity of heat wave events in the North-West region of Iran.